2022
DOI: 10.1016/j.ejso.2021.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic metastases from renal cell carcinoma. Postoperative outcome after surgical treatment in a Spanish multicenter study (PANMEKID)

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 34 publications
1
23
0
1
Order By: Relevance
“…The most extended interval of postoperative pancreatic metastases was 287 months, the 5-year survival was 24.6%, and the 5-year median survival was 24.0% [ 37 ]. Blanco-Fernández et al found that surgery for pancreatic metastases from renal cell carcinoma improved survival [ 38 ]. Chikhladze et al studied surgical and non-surgical treatment of pancreatic metastases and found that surgery improved survival [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most extended interval of postoperative pancreatic metastases was 287 months, the 5-year survival was 24.6%, and the 5-year median survival was 24.0% [ 37 ]. Blanco-Fernández et al found that surgery for pancreatic metastases from renal cell carcinoma improved survival [ 38 ]. Chikhladze et al studied surgical and non-surgical treatment of pancreatic metastases and found that surgery improved survival [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, EUS could detect very small nodules in the pancreas during each preoperative evaluation; therefore, EUS is recommended to determine the appropriate surgical approach. The median interval from primary RCC to PM has been reported to be 83 months, and only 14.3% of patients with PM are symptomatic [8] . EUS is useful for detecting small tumors in the pancreas, and annual EUS is recommended over repeat contrast-enhanced CT to preserve the remnant renal function.…”
Section: Discussionmentioning
confidence: 99%
“…PM from RCC has several distinguishing characteristics, including presentation as an isolated metastasis, slow growth with a long disease-free period after the initial surgery, and a relatively favorable prognosis [6] , [7] . Owing to these characteristics, pancreatic resection is warranted in selected cases to ensure maximal benefits [8] . As repeat pancreatic resection for metachronous PM from RCC is rare, the treatment strategy remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…An accurate preoperative diagnosis is essential to determining a suitable treatment method. Considering the lower prevalence of pancreatic metastasis of liver, lung, bone, or brain metastasis and the long metastatic time between the primary nephrectomy and the metastatic site resection (4,11,(18)(19)(20)(21)(22)(23), accurate diagnoses can be challenging. Enhanced CT is the preferred imaging technique in abdominal examinations, as it can provide detailed information about the tumour's anatomical structure as well as its surrounding area, including the condition of the vasculature.…”
Section: Comparison With Similar Researchmentioning
confidence: 99%
“…No data have clearly demonstrated which candidates should undergo lymphadenectomy for RCC, and many urologists have abandoned lymph node dissection for its lack of proven bene t (32,33). In PmmRCC, some studies demonstrate the same lymph node result of a low rate of lymph node involvement (4,11,19), while others show contrasting results (20,22,23). In Schwarz's report, lymph node involvement was statistically associated with poor overall survival, and Tosoian's study showed no signi cant lymph node ndings, with only increased hazard ratios for mortality (4,22).…”
Section: Comparison With Similar Researchmentioning
confidence: 99%